Eksploitasi Media Terhadap Wanita Dalam Iklan Televisi Perspektif Islam - Muktaruddin Muktaruddin (Hikmah, 2019)
The study is aimed to describe media exploitation againts woman and to analyze based on the communication studies and islamic point of view. The gender equality discourse initiated by women was used by the media to hire women and exploited them for advertising purposes without regard to strong religious norms in society. As the results, it was concluded that the passion of women to get the same rights as men motivated them to agree with the media's policy even though it was more degrading the women. Islam highly upholds the honor of women, glorifies them and protects them. Therefore, according to Islam media's policy againts women is not an honor except an humiliation.